Debridement versus Simple Scrubbing of External Fixator Pin Sites - Nolte, Jack; Dallman, Johnathan; Tucker, William; Christensen, Erin; Heddings, Archie (Kansas Journal of Medicine, 2022)
Introduction. Irrigation and debridement of external fixator pin sites is one method utilized by orthopedic surgeons to prevent surgical site infections in patients undergoing definitive internal fixation after temporization in an external fixation device. This study aims to determine if irrigation and debridement of external fixator pin-sites leads to fewer deep surgical site infections, compared to simply scrubbing the external fixator pin sites with a chlorhexidine scrub-brush. Methods. This single center retrospective cohort study was performed at a University Level I Trauma Center. All cases in which a single surgeon removed an external fixator and followed this with definitive open reduction and internal fixation (ORIF) in the same operative setting between October 2007 and October 2018 were reviewed. 313 patients were temporized in 334 external fixators prior to ORIF and were included in the study. Results. 18 of the 179 Irrigation and Debridement cohort (10.0%) and 8 of the 155 Simple Scrubbing cohort (5.2%) resulted in infections that required return to the operating room. We found no statistical difference (p=0.10) or meaningful effect size (Cohen’s d= 0.18) between irrigation and debridement and simple scrubbing of external fixator pin-sites. Conclusions. Given no significant difference was found between debridement of pin sites versus simply scrubbing, the authors propose further studies should focus on the time and resources required for debriding external fixator pin sites.